2018
DOI: 10.1007/s12311-018-0924-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel Homozygous KCNJ10 Mutation in a Patient with Non-syndromic Early-Onset Cerebellar Ataxia

Abstract: Mutations in KCNJ10, which encodes the inwardly rectifying potassium channel Kir4.1, a primary regulator of membrane excitability and potassium homeostasis, cause a complex syndrome characterized by seizures, sensorineural deafness, ataxia, intellectual disability, and electrolyte imbalance called SeSAME/EAST syndrome. We describe a 41-year-old patient with non-syndromic, slowly progressive, early-onset ataxia. Targeted next-generation sequencing identified a novel c.180 T > G (p.Ile60Met) missense homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…We validated previously reported decrease in the expression of glutamate transporter Slc1a3 in Bergmann glia [70], and identified additional perturbations in the expression of homeostatic genes such as Kcnj10 that are critical for PC function [97][57]. Moreover, our results suggest perturbed Shh signaling as one possible mechanism of these BG molecular alterations.…”
Section: Discussionsupporting
confidence: 86%
“…We validated previously reported decrease in the expression of glutamate transporter Slc1a3 in Bergmann glia [70], and identified additional perturbations in the expression of homeostatic genes such as Kcnj10 that are critical for PC function [97][57]. Moreover, our results suggest perturbed Shh signaling as one possible mechanism of these BG molecular alterations.…”
Section: Discussionsupporting
confidence: 86%
“…Some of the transcriptional changes found in both studies occur in genes encoding potassium channels (Kcnc1, Kcnj10), voltage gated calcium channels (Cacna1b, Cacna1e), and membrane transporters (Slc38a1, Slc39a9) that all have the potential to change the intrinsic excitability of cerebellar Purkinje and nuclei cells. Furthermore, these studies found changes in transcription of genes that are associated with dystonia (Cacna1b, Cacna1e) and ataxia (Car8, Grid2, Grik2, Kcnc1, Kcnj10) (Kaya et al 2011;Utine et al 2013;Groen et al 2015;Guzmán et al 2017;Nicita et al 2018;Helbig et al 2018;. Since these molecular analyses were performed using bulk cerebellar tissue and because Thap1 is universally expressed in the cerebellar circuit, including Purkinje cells, cerebellar nuclei cells and interneurons in the cerebellar cortex, the observed molecular changes could drive changes in the intrinsic excitability and firing patterns of all cerebellar neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the lack of neurological symptoms, as only the kidney shows a complete co-localization of these two subunits. Conversely, no kidney involvement has been found in two patients with a Kir4.1 mutation affecting isoleucine 60 (I60T and I60M; Al Dhaibani et al, 2018 ; Nicita et al, 2018 ), suggesting that in this case, coexpression with Kir5.1 rescues the functional defect. These unusual mutations are colored in pink.…”
Section: East/sesame Syndrome: a Pleiotropic Monogenetic Disease Caus...mentioning
confidence: 82%